2020
DOI: 10.21608/jappmu.2020.102717
|View full text |Cite
|
Sign up to set email alerts
|

Effect of some Protein Sources on White Shrimp Production under Lake Qarun Condition

Abstract: The present study was conducted at Shakshouk Fish Research Station, Fayoum Governorate, National Institute of Oceanography and Fisheries (NIOF), Egypt to investigate the effect of protein sources (fish meal (FM), meat meal (MM), and FM + MM and plant protein (corn gluten meal CGM)) on growth parameter, feed utilization, carcass chemical composition and economic efficiency. Pacific white shrimp (Litopenaeus vannamei) juvenile with an average weight of 3 ±0.13g initial body weight were randomly distributed into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2025
2025
2025
2025

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…They illustrated improving growth performance and feed consumption of Nile tilapia when replacing up to 45% of dietary FM with CGM. Also agrees with Sadek et al [39], who mentioned that a diet containing 75% FM and 25% CGM gave the best FCR, PER, and PPV. In addition, suggested that up to 25% of the fish meal protein could be substituted with CGM in the tilapia fingerlings (Oreochromis niloticus) diet without affecting fish growth or nutrient composition.…”
Section: Discussionsupporting
confidence: 92%
“…They illustrated improving growth performance and feed consumption of Nile tilapia when replacing up to 45% of dietary FM with CGM. Also agrees with Sadek et al [39], who mentioned that a diet containing 75% FM and 25% CGM gave the best FCR, PER, and PPV. In addition, suggested that up to 25% of the fish meal protein could be substituted with CGM in the tilapia fingerlings (Oreochromis niloticus) diet without affecting fish growth or nutrient composition.…”
Section: Discussionsupporting
confidence: 92%